The extragradient algorithm with inertial effects for solving the variational inequality. (1st December 2016) - Dong, Qiao-Li; Lu, Yan-Yan; Yang, Jinfeng
Abstract : In this article, we introduce an algorithms by incorporating inertial terms in the extragradient algorithm. A weak convergence theorem is established for the proposed algorithm. Numerical experiments show that the inertial algorithms speed up the original ones.